2016
DOI: 10.1017/s0025315416001247
|View full text |Cite
|
Sign up to set email alerts
|

Standing stock variations, growth and CaCO3 production by the calcareous green alga Halimeda opuntia

Abstract: The present paper investigates standing stock variations of Halimeda opuntia on a sandstone reef of the South-west Atlantic Ocean, in order to better understand the role of this seaweed as a CaCO3 producer. The study was conducted over two 3-month periods, using photo quadrats to analyse the coverage area, and destructive sampling to quantify area-specific biomass and CaCO3 percentage. The alga occupied 2.4% of the substrate (4464 m2), growing as clumps with an average biomass of 1.59 kg m−2, resulting in a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Recently, Carneiro et al . () showed that Halimeda opuntia can produce at least 13 050.14 kg or 54.37 g m −2 day −1 . Halimeda can also contribute to carbonate sediments with a wide range of sediment grain‐size fractions from coarse sand to silt and clay size (Drew ; Drew & Abel ; Perry et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Carneiro et al . () showed that Halimeda opuntia can produce at least 13 050.14 kg or 54.37 g m −2 day −1 . Halimeda can also contribute to carbonate sediments with a wide range of sediment grain‐size fractions from coarse sand to silt and clay size (Drew ; Drew & Abel ; Perry et al .…”
Section: Introductionmentioning
confidence: 99%
“…), H. opuntia in the tropical South‐west Atlantic Ocean (Carneiro et al . ) and H. macroloba in Thai waters (Sinutok et al . ; Mayakun ; Mayakun et al .…”
Section: Introductionmentioning
confidence: 99%
“…[1] This is a rare marine plants that CaCO3 is synthesized in the tissues (around 35-45 %) at the speed as same as reefs'one. [2] Halimeda incrassata is a potential resource of compounds with a number of valuable bioactivities such as antibacterial, antiinflammation. [3,4] Along with natural products from marine organism, lipid is increasingly recognized because of its positive effects on bones, cardiovascular and nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…It can utilize bicarbonate (HCO 3 − ) for calcification and precipitates aragonite crystals in its intercellular spaces (Borowitzka & Larkum, 1976). It is one of the main calcium carbonate (CaCO 3 ) producers that contribute to the marine carbonate budget in tropical reefs and lagoons (Ree et al ., 2007; Mayakun et al ., 2014; Carneiro & Morais, 2016; Kaewsrikhaw et al ., 2016; McNeil et al ., 2016; Perry et al ., 2016; Carneiro et al ., 2018; Prathep et al ., 2018; Mayakun & Prathep, 2019). For instance, global estimates showed that Halimeda species contributed around 2 kg CaCO 3 m −2 year −1 (Drew & Abel, 1985; van Tussenbroek & van Dijk, 2007; Perry et al ., 2016) or accumulated around 0.15 Gt CaCO 3 year −1 (Milliman, 1993), resulting in ~8% of total world carbonate production (Hillis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, global estimates showed that Halimeda species contributed around 2 kg CaCO 3 m −2 year −1 (Drew & Abel, 1985; van Tussenbroek & van Dijk, 2007; Perry et al ., 2016) or accumulated around 0.15 Gt CaCO 3 year −1 (Milliman, 1993), resulting in ~8% of total world carbonate production (Hillis, 1997). When only tropical reefs are considered, Halimeda can produce ~54.37 g m −2 year −1 of carbonate sediments (Carneiro et al ., 2018), equivalent to at least 13,050.14 kg year −1 or around 42% of total sedimentary organic carbon (Tuntiprapas et al ., 2019). Studies have shown that the carbonate production of Halimeda can vary due to abiotic and biotic factors.…”
Section: Introductionmentioning
confidence: 99%